RISK AND RETURN MANAGEMENT OF SHARIA STOCKS IN JAKARTA ISLAMIC INDEX FOR THE PERIOD OF 2009 – 2019 USING MARKOWITZ PORTOFOLIO MANAGEMENT - Widhiyo Sudiyono (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2021)
To reduce risk in investment and at the same time optimize the returns, it is necessary to establish a series of stocks that have high returns, as well asto select a series of stock with negative variance to reduce the risk. In this research, an efficient frontier approach by Harry Markowitz will be applied to JII shares during the period 2009 - 2019 so that a portfolio with a low risk and optimal return can be formed to reduce risk and optimize return.